Analisis Pemanfaatan AI Untuk Pengembangan Buku Ajar Interaktif di SD IT Anak Sholeh Mandiri Banjarmasin - rasyidan, muhammad; Silvia Ratna; M. Muflih; Herry Adi Chandra; Yusri Ikhwani; Wagino; Nur Alamsyah (Jurnal Inovasi Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the competence of teachers at SD IT Anak Sholeh Mandiri Banjarmasin in utilizing Artificial Intelligence (AI) for the development of interactive teaching materials. In the digital era, AI has great potential to assist teachers in designing learning materials that are more engaging, innovative, and tailored to students’ needs. The training covers the introduction of basic AI concepts, the utilization of various AI-based tools for creating teaching materials, as well as hands-on practice in developing interactive content that can improve learning effectiveness. The methods used include presentations, discussions, workshops, and simulations of AI technology implementation in the creation of teaching materials. It is expected that through this training, teachers at SD IT Anak Sholeh Mandiri Banjarmasin will become more creative and efficient in preparing learning resources, making the learning process more interesting and aligned with technological advancements in education. Moreover, this training also aims to build the school’s readiness to adopt digital technologies in order to support the improvement of education quality.